Pool boiling heat transfer of FC-72 on pin-fin silicon surfaces with nanoparticle deposition. (November 2018) - Cao, Zhen; Liu, Bin; Preger, Calle; Wu, Zan; Zhang, Yonghai; Wang, Xueli; Messing, Maria E.; Deppert, Knut; Wei, Jinjia; Sundén, Bengt
Highlights: Micro-pin-fin surfaces with and without nanoparticle deposition are studied. Surfaces are prepared by an etching method and electrostatic deposition. Pool boiling heat transfer is further improved by nanoparticle deposition. Critical heat flux is further increased by nanoparticle deposition. Abstract: In the present study, two types of micro-pin–fin configurations were fabricated on silicon surfaces by a dry etching method, i.e., staggered pin fins (#1) and aligned pin fins with empty areas (#2). The micro-pin–fin surfaces were then further modified by depositing FeMn oxide nanoparticles (∼35 nm) electrostatically for 8 h and 16 h, respectively, namely #1-8h, #1-16h, #2-8h and #2-16h. Subcooled pool boiling heat transfer was experimentally studied on these surfaces at atmospheric pressure, using FC-72 as the working fluid. The results showed that in comparison to the smooth surface, pool boiling heat transfer was significantly enhanced by the micro-pin-fin surfaces and the maximum superheat was considerably decreased. Additionally, critical heat fluxes were also greatly improved, e.g., the critical heat flux on #1 was almost twice of that on the smooth surface. Generally, the nanoparticle deposition could further enhance pool boiling heat transfer, including the heat transfer coefficient and critical heat flux (CHF). High speed visualizations were taken to explore the mechanisms behind the heat transfer performance. The bubble behavior on the micro-pin–fin surfaces with and without nanoparticles was compared at low, moderate and high heat fluxes, respectively. The wickability of FC-72 on the test surfaces was measured, based on which, a modified CHF model was proposed to predict the experimental CHFs. Accordingly, a possible mechanism of CHF enhancement was described.